2005
DOI: 10.1080/13547500500071339
|View full text |Cite
|
Sign up to set email alerts
|

Scale of classification based on biochemical markers in mussels: application to pollution monitoring in Mediterranean coasts and temporal trends

Abstract: A battery of biochemical parameters was used to evaluate the response of mussels to a contaminated coastal environment. A multimarker approach was developed, establishing a scale for the classification of the water quality in European coastal sites (BIOMAR European programme). This study allows the evaluation of the temporal trends of this scale when applied to selected sites of European Mediterranean coast (BEEP Biological Effects of Environmental Pollution in Marine Coastal Ecosystems: European programme). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 18 publications
2
36
0
3
Order By: Relevance
“…No differences between sampling sites or any clear temporal seasonal trends for GST activity in mussels were observed from the western Mediterranean Sea by Porte et al (2001), neither were they found in a lake and rivers in the Tucholski Landscape Park (central Poland) by Petushok et al (2002). Seasonal changes in CAT activity in mussels have been reported by Solé et al (1995), Regoli (1998), Narbonne et al (1999) and Leiniö and Lehtonen (2005), all showing a higher CAT activity in spring compared to autumn, similar to this study. Bresler et al (1999) observed no differences in GST activity levels of mussels measured from ''clean'' and polluted stations in the German part of the North Sea.…”
Section: Factors Influencing Biomarker Levels In Flounder In the Gulfsupporting
confidence: 76%
“…No differences between sampling sites or any clear temporal seasonal trends for GST activity in mussels were observed from the western Mediterranean Sea by Porte et al (2001), neither were they found in a lake and rivers in the Tucholski Landscape Park (central Poland) by Petushok et al (2002). Seasonal changes in CAT activity in mussels have been reported by Solé et al (1995), Regoli (1998), Narbonne et al (1999) and Leiniö and Lehtonen (2005), all showing a higher CAT activity in spring compared to autumn, similar to this study. Bresler et al (1999) observed no differences in GST activity levels of mussels measured from ''clean'' and polluted stations in the German part of the North Sea.…”
Section: Factors Influencing Biomarker Levels In Flounder In the Gulfsupporting
confidence: 76%
“…Means to assess pollution stress in marine organisms by combining selected biomarkers of exposure and effects have been under recent development (Adams et al, 1993;Narbonne et al, 1999;Beliaeff and Burgeot, 2002;Chèvre et al, 2003a,b;Broeg et al, 2005;Sturve et al, 2005). Environmental deterioration and recovery are processes (Depledge, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The use of integrated biomarker indices is a relatively new approach in the marine ecotoxicological context (Adams et al 1993, Narbonne et al 1999, Beliaeff & Burgeot 2002, Chèvre al. 2003a,b, Broeg & Lehtonen 2006.…”
Section: Integrated Biomarker Response Approachmentioning
confidence: 99%